2018
DOI: 10.3389/fvets.2018.00057
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Benefits of Antibiotics: Tylvalosin Induces Apoptosis of Porcine Neutrophils and Macrophages, Promotes Efferocytosis, and Inhibits Pro-Inflammatory CXCL-8, IL1α, and LTB4 Production, While Inducing the Release of Pro-Resolving Lipoxin A4 and Resolvin D1

Abstract: Excessive accumulation of neutrophils and their uncontrolled death by necrosis at the site of inflammation exacerbates inflammatory responses and leads to self-amplifying tissue injury and loss of organ function, as exemplified in a variety of respiratory diseases. In homeostasis, neutrophils are inactivated by apoptosis, and non phlogistically removed by neighboring macrophages in a process known as efferocytosis, which promotes the resolution of inflammation. The present study assessed the potential anti-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
(109 reference statements)
2
18
0
Order By: Relevance
“…Apoptosis is a form of programmed cell death that has a key role in immune regulation, as controlling the death of immune cells is essential for preventing the destruction of healthy tissues (30). Several antibiotics are able to modulate apoptosis signals in macrophages and neutrophils, which consequently affect both the host and pathogen (33)(34)(35)(36). The regulatory role of apoptosis is significant for the immune response, and disturbances of apoptosis in macrophages and neutrophils have been linked with serious clinical conditions (28,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a form of programmed cell death that has a key role in immune regulation, as controlling the death of immune cells is essential for preventing the destruction of healthy tissues (30). Several antibiotics are able to modulate apoptosis signals in macrophages and neutrophils, which consequently affect both the host and pathogen (33)(34)(35)(36). The regulatory role of apoptosis is significant for the immune response, and disturbances of apoptosis in macrophages and neutrophils have been linked with serious clinical conditions (28,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…However, this may be consistent with the study by Ozkul et al [ 72 ], which found that mice intestinal cells had a high susceptibility to apoptosis after antibiotic and subsequent DSS-colitis treatment. Furthermore, the use of antibiotics alone may have a non-antibiotic effect due to neutrophil apoptosis [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…A disconnect between MIC and clinical efficacy has been previously reported for macrolides against respiratory pathogens in calves and swine [16,17] and this disconnect is reinforced by data presented here. Furthermore, it is well known that macrolides, including tylvalosin, have immunomodulatory effects which may impact in vivo efficacy [18,19]. Increasing evidence demonstrates that tylvalosin exerts such effects by increasing the apoptosis of porcine neutrophils and macrophages, increasing the release of Lipoxin A4 and Resolvin D1, while inhibiting the production and release of pro-inflammatory Leukotriene B4, Interleukin-8 and Interleukin-1α [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is well known that macrolides, including tylvalosin, have immunomodulatory effects which may impact in vivo efficacy [18,19]. Increasing evidence demonstrates that tylvalosin exerts such effects by increasing the apoptosis of porcine neutrophils and macrophages, increasing the release of Lipoxin A4 and Resolvin D1, while inhibiting the production and release of pro-inflammatory Leukotriene B4, Interleukin-8 and Interleukin-1α [18]. These highly complex interactions may have aided the fight against disease.…”
Section: Discussionmentioning
confidence: 99%